2012
DOI: 10.3762/bjoc.8.133
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed substitution of (coumarinyl)methyl acetates with C-, N-, and S-nucleophiles

Abstract: SummaryThe palladium-catalyzed nucleophilic substitution of (coumarinyl)methyl acetates is described. The reaction proceeds though a palladium π-benzyl-like complex and allows for many different types of C-, N-, and S-nucleophiles to be regioselectively added to the biologically active coumarin motif. This new method was utilized to prepare a 128-membered library of aminated coumarins for biological screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…We have recently shown that palladium catalyzes the amination of (coumarinyl)methyl acetates with various amines, including pyrrolidine. 19 Thus, it was somewhat surprising that the benzyl amine product resulting from nucleophilic attack of the amine on the intermediate Pd-π-benzyl complex was never observed (eqn ( 6)). This suggests that enamine formation is faster than ionization of the (coumarinyl)methyl acetate moiety.…”
mentioning
confidence: 99%
“…We have recently shown that palladium catalyzes the amination of (coumarinyl)methyl acetates with various amines, including pyrrolidine. 19 Thus, it was somewhat surprising that the benzyl amine product resulting from nucleophilic attack of the amine on the intermediate Pd-π-benzyl complex was never observed (eqn ( 6)). This suggests that enamine formation is faster than ionization of the (coumarinyl)methyl acetate moiety.…”
mentioning
confidence: 99%